Psychological and ethical implications related to infertility. (5th September 2013) - Minucci, Daria
Abstract: Being a parent is deeply demanding and one of the most important events in life; parents experience the deepening of human relationships with their partner, within their families, and in society, and moreover the fundamental relationship between parent and child. Every medical, social, and political effort must be made to prevent infertility but also to offer infertile couples the best diagnostic and therapeutic paths. Understanding the suffering of the couple and their families prevents and helps ease the possible psychological and social complications of infertility. Therefore, infertility concerns not only biomedical sciences but also psychological and social ones—ethics and law—in their combined efforts to identify areas of understanding and of research for solutions while respecting the dignity of the couple and unborn child. The Catholic Church offers an ongoing contribution through dialogue in looking for ethical principles guiding scientific and medical research respectful of the true life of human beings.